Curling Up With a Good E-Book: Mother-Child Shared Story Reading on Screen or Paper Affects Embodied Interaction and Warmth - Yuill, Nicola; Martin, Alex F. (Frontiers in Psychology, 2016)
This study compared changes in cognitive, affective and postural aspects of interaction during shared mother and child book reading on screen and on paper. Readers commonly express strong preferences for reading on paper, but several studies have shown marginal, if any, effects of text medium on cognitive outcomes such as recall. Shared reading with a parent is an engaging, affective and embodied experience across time, as well as a cognitive task, so it is important to understand how paper vs. screen affects broader aspects of these shared experiences. Mid-childhood sees a steep rise in screen use alongside a shift from shared to independent reading. We assessed how the medium of paper or screen might alter children’s shared reading experiences at this transitional age. Twenty-four 7- to 9-year-old children and their mothers were videotaped sharing a story book for 8 minutes in each of 4 conditions: mother or child as reader, paper or tablet screen as medium. We rated videotapes for interaction warmth and child engagement by minute and analysed dyadic postural synchrony, mothers’ commentaries and quality of children’s recall, also interviewing participants about their experiences of reading and technology. We found no differences in recall quality but interaction warmth was lower for screen than for paper, and dropped over time, notably when children read on screen. Interactions also differed between mother-led and child-led reading. We propose that mother - child posture for paper reading supported more shared activity and argue that cultural affordances of screens, together with physical differences between devices, support different behaviours that affect shared engagement, with implications for the design and use of digital technology at home and at school. We advocate studying embodied and affective aspects of shared reading to understand the overall implications of screens in children’s transition to independent reading.